Exploring EFL Speaking Ability and the Influencing Factors of Middle School Students - Yanik, Seyma; Unal, Burcu (JOURNAL LANGUAGE TEACHING & LEARNING, 2025)
English holds a foreign language status in T & uuml;rkiye, yet proficiency levels remain quite low despite years of formal instruction. In order to better understand this situation, the current study investigated the speaking performance levels of the 7th and 8th grade students, and examined the effects of EFL speaking self-efficacy, speaking anxiety, school type, and out-of-school language practice on speaking performance. The data analysis revealed that while 7th graders met the expected speaking proficiency level, 8th graders fell short of the target level. Additionally, it was found that anxious students tended to have lower speaking self-efficacy. Structural equation modeling showed that while self-efficacy strongly predicted speaking performance, anxiety did not emerge to be a significant contributor. Lastly, private school students demonstrated higher speaking proficiency than public school students, while those who practiced English outside school showed better speaking skills than their peers who did not. These findings suggest the need for policy adjustments that prioritize speaking skills development by fostering supportive learning environments and expanding access to extracurricular language activities that enhance self-efficacy and reduce anxiety. (c) Association of Applied Linguistics. All rights reserved
Keywords: EFL speaking ability; Speaking self-efficacy; Speaking anxiety; Socioeconomic factors; FOREIGN-LANGUAGE ANXIETY; SELF-EFFICACY; ENGLISH; PERFORMANCE; TEACHERS; BELIEFS; REPLICATION; COMMUNICATE; VALIDITY; Education & Educational Research